Digital mindfulness-based intervention for people with COPD – a multicentre pilot and feasibility RCT - Hannah Tschenett; Florian Vafai-Tabrizi; Ralf Harun Zwick; Arschang Valipour; Georg-Christian Funk; Urs M. Nater (Respiratory Research)
Abstract Background Mindfulness-based interventions (MBIs) are effective in improving mental and physical health in various chronic conditions. While the GOLD 2024 report recommends MBIs for chronic obstructive pulmonary disease (COPD), scientific evidence in this specific population is scarce. This prospective randomised controlled pilot study investigated the feasibility of an 8-week digital MBI and its preliminary effects on mental and physical health in COPD. Methods Psychologically burdened COPD patients (63 ± 7 years, 61% female, FEV1% 41 ± 19) were randomly allocated to the MBI group (n = 14; daily 10-15-minute audio-guided meditation via smartphone) or a waitlist control group (n = 16). Primary outcomes included the intervention’s feasibility (dropouts, MBI usage rates, interview and questionnaire responses) and its preliminary effects on symptoms of anxiety and depression (Hospital Anxiety and Depression Scale, HADS). Secondary outcomes included its preliminary effects on the COPD Assessment Test (CAT), Chronic Respiratory Disease Questionnaire (CRQ-SAS), Perceived Stress Scale (PSS-10), and biological stress markers. Exploratory outcomes included momentary subjective stress, anxiety, and dyspnoea after meditating. Results The results indicated that the intervention was feasible (81% usage rate; 93% and 71% found the MBI enjoyable and helpful, respectively), with 21% dropout. A statistically significant intervention (time x group) effect was found for anxiety (HADS-A, p =.010, η p 2  = 0.11) and emotional functioning (CRQ-SAS, p =.004, η p 2  = 0.14), but not for depression (HADS-D, p =.060, η p 2  = 0.06) or any other secondary outcome after 8 weeks. Momentary subjective stress (p <.001, η p 2  = 0.75), anxiety (p =.022, η p 2  = 0.75), and dyspnoea (p <.001, η p 2  = 0.70) were significantly reduced after meditating. Conclusions The digital MBI was feasible, with preliminary effects indicating improvements in anxiety and emotional functioning after 8 weeks as well as momentary outcomes after meditating. Future large-scale trials should further assess the effectiveness of digital MBIs in this context. However, the findings suggest that digital MBIs might be promising and effective low-threshold add-on treatments in clinical settings. Trial registration The article has been preregistered at ClinicalTrials.gov (identifier: NCT04769505, date: 23rd February 2021).